QTLs for cell wall-bound phenolics in relation to the photosynthetic apparatus activity and leaf water status under drought stress at different growth stages of triticale - Hura, Tomasz; Tyrka, Mirosław; Hura, Katarzyna; Ostrowska, Agnieszka; Dziurka, Kinga (Molecular genetics and genomics : MGG, 2017)
The present study aimed at identifying the regions of triticale genome responsible for cell wall saturation with phenolic compounds under drought stress during vegetative and generative growth. Moreover, the loci determining the activity of the photosynthetic apparatus, leaf water content (LWC) and osmotic potential ( Ψ o ) were identified, as leaf hydration and functioning of the photosynthetic apparatus under drought are associated with the content of cell wall-bound phenolics (CWPh). Compared with LWC and Ψ o , CWPh fluctuations were more strongly associated with changes in chlorophyll fluorescence. At the vegetative stage, CWPh fluctuations were due to the activity of three loci, of which only QCWPh.4B was also related to changes in F v / F m and ABS/CS m . In the other QTLs (QCWPh.6R.2 and QCWPh.6R.3), the genes of these loci determined also the changes in majority of chlorophyll fluorescence parameters. At the generative stage, the changes in CWPh in loci QCWPh.4B, QCWPh.3R and QCWPh.6R.1 corresponded to those in DI o /CS m . The locus QCWPh.6R.3, active at V stage, controlled majority of chlorophyll fluorescence parameters. This is the first study on mapping quantitative traits in triticale plants exposed to drought at different stages of development, and the first to present the loci for cell wall-bound phenolics.